THEORETICAL INTERPRETATION OF BUSINESS PROCESSES IN INSURANCE ACTIVITY: GENERALITY AND SPECIFICITY - Khusanov Fakhriddin (American Journals, 2023)
The components of business processes include the creation of new products, sales, services, forecasting, human resource management and other activities aimed at improving operational efficiency.
Keywords: insurance, business, insurance activity, insurance market, professional participants, insurance intermediaries, reengineering business processes.